The Judicial Legacy of Salmond J in New Zealand - Spiller, Peter (Victoria University of Wellington Law Review, 2008)
John Salmond was a judge of the Supreme Court of New Zealand during the years 1920-1924. This paper examines the nature of Salmond J’s contribution to judicial precedent in New Zealand in five areas of the law: administrative; family; procedural; property; and contract law. Salmond J’s judgments in these areas amply justified his reputation as an outstanding jurist. They were characterised by balance, fairness and a keen sense of human reality, and were presented with admirable structure and clarity. Of particular note is Salmond J’s interpretion of the significant body of legislation passed from 1908 onwards. Fortified by his experience of legislative drafting at the time when this legislation was passed, Salmond J confidently supplemented the legislation with case law based on the legislative intent. The overall effect of Salmond J’s judicial work was that, during the eight decades after his death, his judgments provided his successors on the bench with apposite language, frameworks and reference points in the cases before them.